The Role of Peer Support in the Development of Maternal Identity for "NICU Moms". Issue 1 (7th January 2015) - Rossman, Beverly; Greene, Michelle M.; Meier, Paula P.
ABSTRACT Objective To examine first‐time neonatal intensive care unit (NICU) mothers' perceptions of the initial effect and stress of their birth experiences and hospitalizations of their infants and what facilitated or hindered the development of their maternal roles within the context of the NICU. Design A qualitative descriptive design. Setting A 57‐bed, tertiary NICU in Chicago. Participants Twenty‐three mothers of very low birth weight (VLBW) infants hospitalized in the NICU. Methods Participants were a subset of a larger longitudinal mixed‐method study of psychological distress in 69 mothers of VLBW infants. Mothers were interviewed using an adaptation of the Clinical Interview for Parents of High‐Risk Infants (CLIP) approximately 6 weeks after the births of their infants. Data were analyzed using conventional content analysis. Results Mothers characterized the infants' births and hospitalizations as a time of overwhelming change culminating in a new perspective on life. Primary themes were loss, stress and anxiety, adapting, resilience, peer support, and "I'm a NICU Mom." Mothers rated peer support as the most facilitative and supportive aspect of developing the maternal role in the NICU. Conclusion Peer support and role modeling by NICU‐based breastfeeding peer counselors helped the mothers throughout every stage of their infants' hospitalizations, from giving them hope, to helping them begin to develop maternal identity, to providing anticipatory guidance about taking their infants home. Talking points are provided for nurses who work in NICUs without dedicated peer support to help mothers establish a healthy mother/infant relationship.